PENGEMBANGAN DESAIN BAHAN AJAR CETAK BERBASIS MULTIMEDIA UNTUK MENDUKUNG PEMBELAJARAN MANDIRI DI UNIVERSITAS TERBUKA: DEVELOPMENT OF MULTIMEDIA-BASED PRINT TEACHING MATERIAL DESIGN TO SUPPORT INDEPENDENT LEARNING AT OPEN UNIVERSITY - Bangun Asmo Darmanto; Drajatno Widi Utomo; Agung Eko Budiwaspada (Universitas Trisakti, 2025)
Development of Multimedia-Based Print Teaching Material Design to Support Independent Learning at the Open University. Development of Multimedia-Based Print Teaching Material Design to Support Independent Learning at the Open University. This research aims to increase the effectiveness of self-learning in Entrepreneurship in the Digital Era course for Open University students, especially in the 3T region. The printed teaching materials that have been used are considered less than optimal in utilizing information technology and visual communication design, thus hindering students' understanding of dynamic entrepreneurship concepts. The development of information technology offers significant potential to support the development of innovative multimedia-based printed teaching material designs by combining the concept of hypercontent and QR Code features. Hypercontent allows students to access additional materials, video tutorials, and business simulations interactively. Meanwhile, the QR Code will connect students with relevant online learning resources, such as journal articles, case studies, and discussion forums. The research method used is Research and Development (R&D) with the Four-D model (Define, Design, Develop, Disseminate). The development of multimedia-based print teaching materials is expected to increase the effectiveness of independent learning and facilitate understanding of the material for students. This study provides several recommendations for further development, including: (1) a variety of more interesting visual and graphic elements to enrich the material content, (2) exploration of other interactive features such as videos, animations, or mini-quizzes to increase student engagement, and (3) utilization of link codes or URLs in the form of QR codes that lead to relevant and up-to-date learning resources. Thus, the multimedia-based print teaching materials developed in this study have great potential to be an effective and flexible learning media, especially for Open University students who study independently. It is expected that with this innovative teaching material design, student learning motivation will increase, understanding of entrepreneurship concepts will be deeper, and students' ability to apply the knowledge gained will be better.